IN THE RING AND ONLINE: RELATIONAL LABOR AND AUDIENCE ENGAGEMENT IN THE WWE - Lingel, Jessa (AoIR Selected Papers of Internet Research, 2020)
Professional wrestling has long been of interest to cultural and media theorists (Barthes, 2015; Canella, 2016; Olson, 2018). Long before reality TV, the performativity and scripted drama of professional wrestling allowed theorists to unpack questions of fictionality and narrative authenticity. In the context of internet studies, professional wrestling raises additional questions: How do performers use social media to maintain relationships with fans? How do gender norms manifest in on-stage versus online performances of professional identity? In this extended abstract, I present key concepts and guiding research questions for an investigation of fan culture and gender norms. I then provide a brief overview of related work and describe my mixed-methods approach. As this research project is ongoing, I present preliminary findings and implications as a concluding section.